Human factors required for mycobacterium tuberculosis macrophage infection - Carmo, Nuno Baltazar do, 1976- (2016)
Tese de doutoramento, Farmácia (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Farmácia, 2014